Efficacy and safety of cardiac myosin inhibitors for symptomatic hypertrophic cardiomyopathy: a meta-analysis of randomized controlled trials - Abunada, Anas; Shah, Madiha; Kumar, Ateesh; Lamiya Mir, Syeda; Kumar, Dinesh; Ahmed, Saboor; Tanzeel, Muhammad; Kumar, Vikash; Meghjiani, Aashish; Siddiqui, Muhammad Basit Ali; Khatri, Govinda; Rai, Aneesh; et al. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionHypertrophic cardiomyopathy (HCM) is a common genetic heart disorder. It is characterized by left ventricular hypertrophy and impaired cardiac function, with forms categorized into obstructive (oHCM) and nonobstructive (nHCM). Traditional treatments address symptoms but not the underlying disease mechanism, highlighting the need for novel therapies. Cardiac myosin inhibitors such as mavacamten and aficamten present potential new treatment options.MethodsA meta-analysis of randomized controlled trials (RCTs) was conducted following PRISMA guidelines. Studies comparing cardiac myosin inhibitors with placebo were reviewed, and outcomes related to NYHA functional class, Kansas City Cardiomyopathy Questionnaire Clinical Summary Score (KCCQ-CSS), LVOT gradients, and left ventricular ejection fraction (LVEF) were analyzed.ResultsSix RCTs involving 826 participants demonstrated that mavacamten and aficamten significantly improved NYHA functional class and KCCQ-CSS scores. The incidence of treatment-emergent adverse events (TEAEs) and serious adverse events (SAEs) was similar between the treatment and control groups, indicating a comparable safety profile.ConclusionCardiac myosin inhibitors are effective in improving cardiac function and reducing LVOT obstruction in HCM patients. They offer a promising alternative to current treatments, with a safety profile comparable to placebo. Further research is needed to confirm long-term benefits.